2009
DOI: 10.1016/j.ymssp.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

On the energy leakage of discrete wavelet transform

Abstract: The energy leakage is an inherent deficiency of Discrete WaveletTransform (DWT) which is often ignored by researchers and practitioners. In this paper, a systematic investigation into the energy leakage is reported. The DWT is briefly introduced first, and then the energy leakage phenomenon is described using a numerical example as an illustration and its effect on the DWT results is discussed.Focusing on the Daubechies wavelet functions, the band overlap between the quadrature mirror analysis filters was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 22 publications
(15 reference statements)
0
27
0
3
Order By: Relevance
“…By doing so, the latter represented the original reflectance with a limited number of coefficients without causing significant errors for signal representations (loss of 0.01% of total energy). One of the important properties of DWT is that the energy of the Gaussian noise component of the signal will usually be dispersed as relatively small coefficients [54]. Hence, getting rid of the low coefficients might also have helped us eliminate the noise.…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, the latter represented the original reflectance with a limited number of coefficients without causing significant errors for signal representations (loss of 0.01% of total energy). One of the important properties of DWT is that the energy of the Gaussian noise component of the signal will usually be dispersed as relatively small coefficients [54]. Hence, getting rid of the low coefficients might also have helped us eliminate the noise.…”
Section: Discussionmentioning
confidence: 99%
“…In the j-th level, low-frequency components are limited in the interval . Note that the precise frequency spectrum partition is impractical, since the filters frequency responses should be ideal (Peng et al, 2009 As suggested by Peng et al (2009), the upper limit for the approximation coefficients is higher than 25 Hz, which is the frequency of interest. Therefore, setting the sampling rate at 125 Hz is suitable.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Therefore, if s f is the sampling frequency, the frequency contents for approximation and detail coefficients, in the j -th decomposition level, are in the interval  , respectively. In practice, the ideal cut-off frequencies are not realizable (Peng et al, 2009 . Hence, there is a band overlap.…”
Section: Discrete Wavelet Transformmentioning
confidence: 99%
“…The differences in the wavelet spectrum observed at time scales near the annual cycle (Fig. 4c) likely result from the ''leakage of the energy'' (in this case toward the strong annual and semiannual cycles) commonly associated with discrete wavelet transforms (Peng et al 2009). The wavelet power spectrum of CEOF-2 was obtained using the Morlet wavelet base function [see Torrence and Compo (1998) for details on the wavelet transform].…”
Section: A Definitionmentioning
confidence: 98%